Political Actions of Islamic Boarding School Students in the 2024 Elections: A Study of Traditional and Modern Islamic Boarding Schools - Sayekti, Anggalih; Faradibah, Putri Annisya; Amallya, Zahwa (Journal of Political Islam, 2025)
ABSTRACT Political action is an effort undertaken by individuals or political groups to achieve certain goals. Santri, as a group of people living in a pesantren without digital access, certainly find it more difficult to receive information or the latest news that is currently trending outside, especially regarding election activities, so it is highly likely that there will be changes in the political behavior of the santri group. This study aims to discuss the political actions of santri at the Mambaul Maarif Denanyar Jombang Islamic Boarding School, a traditional Islamic boarding school, and the Darussalam Ngesong Sengon Jombang Islamic Boarding School, a modern Islamic boarding school, in the 2024 Presidential Election. This research was conducted using a literature study method to collect information sources. The results of the study show that there are differences in political actions at the Mambaul Maarif Denanyar Islamic boarding school, where the majority of students choose candidates with a strong religious background, and the organizations and parties that support them are also considered to be as closely related to Islam as possible. The students’ obedience to the kiai is very strong in determining their political choices, so that every choice made by the kiai is a reference for his students and cannot be opposed. In contrast, at the Darussalam Ngesong Sengon Islamic boarding school, students are given the freedom to make their own choices, because the kiai is rational and does not feel that he has the right to determine his students’ choices.